Reducing the solubility of the major birch pollen allergen Bet v 1 by particle-loading mitigates Th2 responses - Amin Kraiem; Erica Pelamatti; Sophie Grosse-Kathoefer; Hilal Demir; Ute Vollmann; Caroline Ehgartner; Maria Stigler; Benjamin Punz; Litty Johnson; Nicola Hüsing; Barbara Bohle; Lorenz Aglas (Allergology International)
Background: Solubility is a common feature of allergens. However, the causative relationship between this protein-intrinsic feature and sensitization capacity of allergens is not fully understood. This study aimed to proof the concept of solubility as a protein intrinsic feature of allergens. Methods: The soluble birch pollen allergen Bet v 1 was covalently coupled to 1 μm silica particles. IgE-binding and -cross-linking capacity was assessed by inhibition ELISA and mediator release assay, respectively. Alterations in adjuvanticity by particle-loading were investigated by activation of dendritic cells, mast cells and the Toll-like receptor 4 pathway as well as by Th2 polarization in an IL-4 reporter mouse model. In BALB/c mice, particle-loaded and soluble Bet v 1 were compared in a model of allergic sensitization. Antigen uptake and presentation was analysed by restimulating human Bet v 1-specific T cell lines. Results: Covalent coupling of Bet v 1 to silica particles resulted in an insoluble antigen with retained IgE-binding and -cross-linking capacity and no increase in adjuvanticity. In vivo, particle-loaded Bet v 1 induced significantly lower Bet v 1-specific (s)IgE, whereas sIgG1 and sIgG2a levels remained unaffected. The ratio of Th2 to Th1 cells was significantly lower in mice sensitized with particle-loaded Bet v 1. Particle-loading of Bet v 1 resulted in a 24-fold higher T cell activation capacity in Bet v 1-specific T cell lines, indicating more efficient uptake and presentation than of soluble Bet v 1. Conclusions: Our results show that solubility is a decisive factor contributing to the sensitization capacity of allergens. The reduction in sensitization capacity of insoluble, particle-loaded antigens results from enhanced antigen uptake and presentation compared to soluble allergens.